IMPACT OF SOCIAL MEDIA ON FASHION AND CONSUMER BEHAVIOUR (A SURVEY BASED STUDY) - Walia, Charan Kamal (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Social media has brought industry connectedness, innovation, and diversity to fashion. Instagram, for example, functions like a live magazine that is constantly updated with the best and latest trends, allowing users to participate in fashion rather than just viewing watches from afar. Social media has done incredible several things for the fashion industry: It has spawned fashion icons, greatly influenced heavy fashion trends, and ultimately reformed the way people apply for jobs in the field. Traditionally, before social media, becoming a fashion icon was next to impossible. Fashion industry employees had to see you and think you were incredible. They had to build your brand from scratch. Unless you had fame from other experiences, your journey entailed audition after audition, deal after deal, catwalk after catwalk, and after all of which you would still only have the slightest chance of becoming a recognizable fashion figure. But social media has changed the game. Users are getting themselves discovered instead of waiting for someone to discover them. With new tools like Instagram, users build their brands and find their fans and followers. Instagram has exposed average people to opportunities they otherwise would not have. Gone are the days when formal dressing would be used to highlight one’s personality. Fashion and style now take centre stage. But the million-dollar question that begs to ask is: who or what primarily determined what today’s young men and women choose to wear and why. Well, the simple and straight answer is fashion channels, fashion media, and social media.